Physical Properties of Bioplastic Composite Synthesized from Sago Waste and Betung Bamboo Activated Carbon - Aprilianda, Aprilianda; Budiman, Ismail; Kurniati, Mersi; Sari, Yessie Widya (Universitas Al Azhar Indonesia, 2023)
Bioplastics are expected to reduce the use of commercial plastics. Several efforts have been made to improve the properties of bioplastics, including the addition of antioxidants or antimicrobial agents. One of the antimicrobial agents is activated charcoal or activated carbon. This study was aimed to investigate the effect of activated carbon addition to the bioplastic composite. Sago waste was utilized as the matrix in the composite, while activated carbon was as filler. Sago waste is the leftover biomass resulted from the sago extraction. The proximate analysis showed that the composition of sago waste was mostly dominated by the fibrous materials followed by protein and fat. The activated carbon was obtained from the treatment of Betung bamboo. The Fourier Transform Infrared (FTIR) spectroscopy indicated that the thermal treatment of Betung bamboo at 175 °C for 5 h resulted The treated sago waste was immersed in 5% KOH for 24 h and further dried and then pyrolyzed at 750 °C for 90 min to yield activated carbon. The activated carbon was dominated by the carbonaceous materials. This was also supported by the proximate data indicating the presence of 91% carbonaceous materials in activated carbon. The Brunauer Emmett Teller (BET) analysis showed that the activated carbon has surface area of 460 m2/g. This activated carbon was then used as filler at bioplastic composites. Two levels of activated carbon percentage on composite were tested, which were 3-5% (% m/v). The mechanical analysis using universal testing machine indicated that the addition of activated carbon reduces the tensile strength and modulus of elasticity. The scanning electron microscopy (SEM) images clearly indicated the presence of activated carbon on the surface of bioplastics. The data obtained in this study showed the potential of composite sago waste and activated carbon as bioplastics. Further, the activated carbon obtained in this study can serve as an adsorbent, providing possible applications as antibacterial agent. Keywords – Activated Carbon, Biomass, Bioplastic, Composite, Pyrolysis, Sago Waste.